Repurposing Standardized Testing for Educational Equity: Can Geographical Bias and Adversity Scores Expand True College Access?. (October 2019) - González Canché, Manuel S.
Recent Federal Bureau of Investigation (FBI) criminal charges involving standardized testing have renewed public scrutiny over the tests' role in reproducing inequities and wealth-based privileges. Although some continue to call for the eradication of standardized testing, this article presents a different perspective with a threefold purpose. First it provides a critical review of the existing literature on standardized testing including the newest development: geographical bias in testing or the systemic and systematic ways in which place-based resources influence test-takers' performance. Second, it discusses the goals and consequences of the College Board's recently unveiled "adversity score, " designed as a tool to "boost admission prospects" of students facing additional challenges in their neighborhoods and schools. Finally, it offers a conceptual and methodological framework and policy insights to shift the role of these tests as reproducers of inequalities to enhancers of equity and opportunity into what is termed true college access : enrollment with realistic prospects of success.